Web 2.0 : a strategy guide - Shuen, Amy. (Beijing : O'Reilly, 2008)
This guide explains what's different about Web 2.0 and how those differences can improve your company's bottom line.
Chapter 1. Users Create Value.--Chapter 2. Networks Multiply Effects.--Chapter 3. People Build Connections.--Chapter 4. Companies Capitalize Competences,--Chapter 5. New Recombines with Old.--Chapter 6. Business Incorporate Strategies.
Includes bibliography and index.
Keywords: MANAGEMENT INFORMATION SYSTEMS; PROJECT MANAGEMENT -- DATA PROCESSING; COMPUTER SOFTWARE -- DEVELOPMENT; INFORMATION TECHNOLOGY -- MANAGEMENT; ELECTRONIC COMMERCE; WEB 2.0.; STRATEGIC PLANNING; BUSINESS PLANNING